2008
DOI: 10.1177/8756479308315234
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Detection Rate of Normal Fetal Cardiac Structures: A Real-Time Approach

Abstract: The use of sonographic imaging for routine fetal screening in the second trimester has been adopted by the Canadian health care system and a number of European countries as a standard of care. 1 According to a survey of 2758 referrals to the fetal cardiology unit at Guy's Hospital,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Not included in our study, however, was the 3‐vessel view, which has been found to be a very effective method of assessing the ventricular outflow tracts 17 . In a pilot study, it was found that most screening centers in our region were acquiring the 4‐chamber and outflow views as 3 still images, and the acquisition of the 3‐vessel view increased the acquisition time substantially compared with the 2 sweeps described above 18 . Our approach is intended to incorporate cine loop sweeps into a routine second‐trimester sonographic examination with a minimum of additional acquisition time and sonographer training, and for this reason, we chose not to include the 3‐vessel view.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Not included in our study, however, was the 3‐vessel view, which has been found to be a very effective method of assessing the ventricular outflow tracts 17 . In a pilot study, it was found that most screening centers in our region were acquiring the 4‐chamber and outflow views as 3 still images, and the acquisition of the 3‐vessel view increased the acquisition time substantially compared with the 2 sweeps described above 18 . Our approach is intended to incorporate cine loop sweeps into a routine second‐trimester sonographic examination with a minimum of additional acquisition time and sonographer training, and for this reason, we chose not to include the 3‐vessel view.…”
Section: Discussionmentioning
confidence: 95%
“…17 In a pilot study, it was found that most screening centers in our region were acquiring the 4-chamber and outflow views as 3 still images, and the acquisition of the 3-vessel view increased the acquisition time substantially compared with the 2 sweeps described above. 18 Our approach is intended to incorporate cine loop sweeps into a routine second-trimester sonographic examination with a minimum of additional acquisition time and sonographer training, and for this reason, we chose not to include the 3-vessel view. The abnormal cases were acquired in a prospective fashion based on availability to the researchers; therefore, they do not rep- Data are presented as number (percent).…”
Section: Discussionmentioning
confidence: 99%
“…37 In a pilot study, Scott et al examined the potential for including a color Doppler cineloop of the three-vessel view in a routine obstetric screening protocol. 38 The results of this study determined that the color cineloop lengthened the examination time significantly and adversely affected the quality of the gray-scale features due to bleeding of color and to challenges associated with optimizing the color Doppler controls. 38…”
Section: Color Dopplermentioning
confidence: 92%
“…In over 50% of normal studies, at least two of the four pulmonary veins will be seen, usually one from each lung. 23 Two ventricles should be seen, approximately the same size, with symmetry in wall thickness and contractility. The right ventricle will become slightly larger than the left ventricle as pregnancy progresses.…”
Section: Stepmentioning
confidence: 99%
“…A number of authors have identified the use of cineloops as a practical means of improving the assessment of the fetal heart. [21][22][23] Acquiring cine-loops as compared to still images only has the potential to significantly increase the visualization rate of normal fetal heart structures. 23 A standardized assessment can be performed if the image acquisition process is well structured and includes cine-loops.…”
Section: Standardized Assessmentmentioning
confidence: 99%